How to protect Chinese medicine prescription more effectively? - Liu, Xiaochang; Zhai, Gaoyuan (Frontiers in Pharmacology, 2025)
As an important carrier of traditional Chinese medicine (TCM) knowledge, TCM prescriptions is the crystallization of the wisdom of Chinese medical practitioners through the ages, and occupies a pivotal position in the traditional knowledge system of Chinese medicine in China. However, under the current legal framework, despite the establishment of intellectual property rights system and the adoption of the Law of the People’s Republic of China on Traditional Chinese Medicine, which provide a certain legal foundation for the protection of TCM, these systems still face difficulties in providing adequate and effective protection for TCM prescriptions in practical operations. Based on this, this paper will adopt the comparative research method and literature analysis method to deeply explore advanced systems in other countries for the protection of traditional medicine knowledge and to identify the shortcomings and deficiencies of the current systems in China. On this foundation, the paper will focus on discussing how to improve and upgrade China’ TCM prescription protection system through both active improvement measures and passive defence measures. The goal is to prevent improper utilization of China’s TCM prescriptions by other countries while also facilitating China’s TCM enterprises to enter the international arena, enhancing China’s national influence and voice in the field of TCM, and contributing wisdom and strength to the inheritance and development of the TCM industry.